ANALYSIS OF CONSUMER PREFERENCES IN CONSUMING PROCESSED COFFEE PRODUCTS AT CAFE NECTAR BALI - Isabel Divya Georgiana Walewangko; I Komang Gde Sukarsa; I Gusti Ngurah Lanang Wijayakusuma; I Putu Eka Nila Kencana; I Gusti Ayu Made Srinadi; Ratna Sari Widiastuti (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Coffee beverages have become a highly sought-after product, particularly in tourist areas that are favoured by both local and foreign tourists. For this reason, there are many business owners who want to expand their business with coffee as the main menu. Cafe Nectar Bali, not far from the tourist attraction Garuda Wisnu Kencana (GWK), is one of the places frequented by both locals and foreign tourists. The purpose of this study is to identify the characteristics consumers often consider when consuming processed coffee products at Cafe Nectar Bali and to understand the preferences of local residents and foreign tourists regarding processed coffee products offered. The research method used is the analysis of local and foreign tourist preferences using conjoint analysis techniques. The findings show that consumers are prioritizing the type of coffee and how it is served. Both locals and foreign tourists value the diversity feature more than the presentation method feature. Local consumers choose the stimulus of latte variant and hot serving methods. On the other hand, foreign tourists chose the stimulus of latte variant and the cold serving method. Coffee; Conjoint Analysis; Consumer Preferences